Using of ASTER, ETM+ and Gamma Spectrometry Airborne Data to Find the Relationship Between the Distribution of Alkali Metasomatism and REE Mineralization in the Bafq Area, Central Iran - K. Khoshnoodi; M. Yazdi; M. Behzadi; M. Gannadi-Maragheh (Journal of Sciences, Islamic Republic of Iran)
The study area is located in the central Iranian tectono-magmatic zone, which is known for its world-class IOA-type Iron ore deposits. The Advanced Space borne Thermal Emission and Reflection Radiometer (ASTER) and Landsat Enhanced Thematic Mapper Plus (ETM+) image-processing techniques, were used in satellite imagery through conventional and also modern processing methods including band ratios, color composite ratio images and spectral angle mapper to study the spectral discrimination of metasomatically altered rocks based on their mineral assemblages and to investigate critically the link between the distribution of Na-metasomatism and occurrence of REE mineralization through plotting the image processing results on preexisting airborne radiometric data. The achieved information points the matter that the distribution of the metasomatized rocks, in common, and Na-metasomatized rocks, in particular, are coincide with the areas with high radioactivity revealed during an airborne radiometry program. A stage of field study associated with ground spectrometry survey carried out to control some localities and showed such correlation mainly around and within some magnetite ore deposits through which two phases of albitization were revealed, namely, a widespread albitization phase within which the spectrometric survey showed normal amounts of radioactive elements and another phase that affected smaller areas and showed REE anomaly and the Na-metasomatites of which are, experimentally, more reddish in colure (meaty color in hand specimens). The Iron deposits are, chronologically, hosted in upper Proterozoic-lower Cambrian volcano-magmatic units associated with a widespread phase of Na-metasomatism, economically, resulted in enrichment of the host rocks in REE bearing mineral phases.